Laplace Transform
Laplace Transform
Laplace Transform
INTRODUCTION
Laplace transform is one of the tool or method for analyzing
circuits with sinusoidal or non-sinusoidal input.
Laplace transform id used to transform the circuit from the
time domain to the frequency domain and obtain the solution.
Then, apply inverse Laplace transformation to transform it
back to the time domain.
The advantages using Laplace transform is it can be applied
to variety of input and its provides an easy way to solve
circuits equation or problems that involving initial condition
and without differential equation.
Definition & Properties of Laplace
Transform
For a function of t, f(t), its laplace
transform is given by a definition equation
below;
}
= =
0
) ( ) ( )] ( [ dt e t f s F t f L
st
) ( ) ( s F t f
Properties of Laplace Transform
goI
EXAMPLE
( ) ( ) ( )
t
e t u t t f
2
3 2
+ = o
Find the Laplace transform of the :
( ) ( ) | | ( ) | | | |
t
e L t u L t L s f
2
3 2
+ = o
Refer to Laplace transform table
Exercise
Find the Laplace transform for :
a)
b)
c)
( )
t
e t t f
3
2 cos
+ =
( )
t
te t t f
2
5 2 sin 2
+ =
( ) t e t f
t
3 cos
2
=
Inverse Laplace transform
Inverse Laplace transform is the way how to transform
back to the time domain from frequency domain and
obtain the corresponding f(t).
However, finding the inverse laplace transform of F(s)
become easier by apply the following two steps;
decompose F(s) into simple terms using partial fraction
expansion.
find the inverse of each term by matching entries in
table
( ) | | ) (
1
t F s F L =
Step
1
Example 1
) 3 ( ) 2 ( ) 3 )( 2 (
12
2
+
+
+
+ =
+ +
+
s
C
s
B
s
A
s s s
s
Find the inverse Laplace of:
) 3 )( 2 (
12
2
+ +
+
s s s
s
Step
2
Find value of A,B and C
Find value A,B,C
2
) 3 )( 2 (
12
) 3 )( 2 (
12
| ) (
0
2
0
= =
+ +
+
= =
=
=
s
s
s s
s
s sF A
8
) 1 )( 2 (
12 4
) 3 )( (
12
| ) ( ) 2 (
2
2
2
=
+
=
+
+
= + =
=
=
s
s
s s
s
s F s B
7
) 1 )( 3 (
12 9
) 2 )( (
12
| ) ( ) 3 (
3
2
3
=
+
=
+
+
= + =
=
=
s
s
s s
s
s F s B
So
refer table to find the inverse Laplace
for
) 3 (
7
) 2 (
8 2
) 3 )( 2 (
12
) (
2
+
+
+
=
+ +
+
=
s s s s s s
s
s F
Step
3
(
+
+
(
=
) 3 (
7
) 2 (
8 2
) (
1 1 1
s
L
s
L
s
L t f
t t
e e t f
3 2
7 8 2 ) (
+ =
Example 2
Find the inverse Laplace of:
Give your attention to partial fraction !!!
) 4 ( ) 4 ( ) 1 ( ) 4 )( 1 (
4 10
) (
2 2
2
+
+
+
+
+
+ =
+ +
+
=
s
D
s
C
s
B
s
A
s s s
s
s F
Find value of A,B and C
A=1/4
B=-14/9
C=41/3
The step same as
example 1
How to find D
4
2
2
4
2
4 10
) ( ) 4 (
=
=
|
|
.
|
\
|
+
+
= + =
s
s
s s
s
ds
d
s F s
ds
d
D
s du
s u
20
4 10
2
=
+ =
1 2
2
+ =
+ =
s dv
s s v
( )
13
4
132 80
) (
) 1 2 )( 4 10 ( ) 20 (
4
2 2
2 2
2
=
+
=
+
+ + +
=
= s
s s
s s s s s
v
udv vdu
So
t t t
e te e t u t f
s
L
s
L
s
L
s
L t f
2 2
1
2
1 1 1
13 22 14 ) ( ) (
) 4 (
13
) 4 (
22
) 1 (
14 1
) (
+ + =
(
+
+
(
+
+
(
=
Example 3
) 25 8 ( ) 3 ( ) 25 8 )( 3 (
20
) (
2 2
+ +
+
+
+
=
+ + +
=
s s
C Bs
s
A
s s s
s F
( ) 2
10
20
) 25 8 (
20
| ) ( 3
3
2
3
= =
+ +
= + =
=
=
s
s
s s
s F s A
Find B and C
Create 2 equation for any value of s (
s-3)
10
3
50 20
2
20 3 25
25
) 0 (
3 ) 75 (
20
) 25 8 ( ) 3 ( ) 25 8 )( 3 (
20
) (
0
2 2
=
=
=
= +
+
+ =
+ +
+
+
+
=
+ + +
=
=
C then
A
C A
so
C B A
s s
C Bs
s
A
s s s
s F
s f or
2
4
68 40 20
10
2
20 4 4 34
34 4 ) 34 ( 4
20
) 25 8 ( ) 3 ( ) 25 8 )( 3 (
20
) (
1
2 2
=
+
=
=
=
= + +
+
+ =
+ +
+
+
+
=
+ + +
=
=
B then
C
A
C B A
so
C B A
s s
C Bs
s
A
s s s
s F
s f or
So
t e t e e t f
s s
s
s
s s
s
s
s
s
s
s s
s
s s s s
s F
t t t
3 sin
3
2
3 cos 2 2 ) (
9 ) 4 (
3
3
2
9 ) 4 (
) 4 ( 2
) 3 (
2
9 ) 4 (
2
9 ) 4 (
) 4 ( 2
) 3 (
2
9 ) 4 (
2 ) 4 ( 2
) 3 (
2
) 25 8 (
10 2
) 3 (
2
) 25 8 )( 3 (
20
) (
4 4 3
2 2
2 2
2
2 2
=
+ +
+ +
+
+
=
+ +
+ +
+
+
=
+ +
+ +
+
=
+ +
+
+
=
+ + +
=
Exercise
) 3 )( 5 4 (
1
) (
) 2 )( 1 (
4 2
) (
) 3 )( 2 )( 1 (
10
) (
2
2
2
2
+ + +
+
=
+ +
=
+ + +
=
s s s
s
s F
s s
s s
s F
s s s
s
s F
Determine the inverse Laplace transform for each of the following function
= ) t ( f
-3t -2t -t
e 15 e 20 e 5 - +
= ) t ( f
-2t -t
e ) t 2 1 ( 6 e 7 +
= ) t ( f
) t cos( e 4 e 5
-2t -3t
= ) t ( f
-3t -2t -t
e 15 e 20 e 5 - +
= ) t ( f
-2t -t
e ) t 2 1 ( 6 e 7 +
= ) t ( f
) t cos( e 4 e 5
-2t -3t